Accelerator Mass Spectrometry 14C Dating and the Antiquity of Shell-Tempered Ceramics from the Chesapeake Bay and Middle Atlantic. Issue 3 (20th July 2013) - Rick, Torben C.; Lowery, Darrin L.
Abstract: Ceramics typologies have long been used to build artifact, site, and regional chronologies. Direct accelerator mass spectrometry (AMS) 14 C dating of shell-tempered ceramics offers a promising tool for updating and improving these chronologies. Few studies have 14 C dated shell fragments from shell-tempered pottery, however, and questions remain about potential biases from "old shell, " the reservoir effect, and other variables. Forty-five direct AMS 14 C assays on shell-tempered pottery and associated shell, charcoal, and bone from nine archaeological sites in Virginia and Maryland provide a framework to test this method. AMS 14 C assays from one site may have problems with old shell, but most of the calibrated direct and associated age estimates overlap. One of our samples is the oldest securely dated shell-tempered pottery in North America at 1000 cal B.C. Our study demonstrates the promise of AMS 14 C dating shell-tempered pottery for refining ceramic and regional chronologies in coastal and other areas around the world.